2017
DOI: 10.1016/j.pnpbp.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Prior treadmill exercise promotes resilience to vicarious trauma in rats

Abstract: Background Post-traumatic stress disorder (PTSD) is a serious psychological condition, which can develop both from physically experiencing and also from witnessing traumatic events. There is evidence that physical exercise can have a positive impact on the symptoms of PTSD. Relevant to this, in our previous pre-clinical work, beneficial effects of treadmill exercise were reported on PTSD-like behaviors in a social defeat paradigm, a rat model of direct physical trauma. However, the role of exercise on vicariou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
(76 reference statements)
1
11
0
Order By: Relevance
“…Besides, various social defeat stress rat models have been developed in recent years, including the CSDS and psychosocial witness stress rat model (Patki, Solanki, & Salim, 2014). Existing studies have shown that behavioral and physiologic characteristics of these rat models are similar to those in mouse models (Arora et al, 2018;Finnell et al, 2018;Giacobbo et al, 2020;Kochi et al, 2017;Morais-Silva et al, 2019;Zaidi et al, 2020), which further confirms the feasibility of CSDS-induced behavioral deficits among different strains.…”
Section: Perspectivementioning
confidence: 77%
“…Besides, various social defeat stress rat models have been developed in recent years, including the CSDS and psychosocial witness stress rat model (Patki, Solanki, & Salim, 2014). Existing studies have shown that behavioral and physiologic characteristics of these rat models are similar to those in mouse models (Arora et al, 2018;Finnell et al, 2018;Giacobbo et al, 2020;Kochi et al, 2017;Morais-Silva et al, 2019;Zaidi et al, 2020), which further confirms the feasibility of CSDS-induced behavioral deficits among different strains.…”
Section: Perspectivementioning
confidence: 77%
“…LD test detects anxiety indicated by avoidance of lit areas, but EPM test detects anxiety-like behavior that results from avoidance of open, lit and elevated areas. Thus, while rats at PND60 did not exhibit anxiety-like behavior in LD test, which is a mild test (Salim et al, 2010), anxiety-like phenotype was evident in a more stringent EPM test (Kochi et al, 2017). Additionally, SD did not impact the high sociability behavior in rats (Figure 5).…”
Section: Discussionmentioning
confidence: 91%
“…For instance, studies have reported that mice or rats observing traumatic events, in this case conspecifics subjected to repeated social defeat, elicited enhanced avoidance of open arms ( Sial et al, 2016 ; Kochi et al, 2017 ), affecting ( Patki et al, 2014 , 2015 ), or not ( Warren et al, 2013 ), the general locomotor activity in the open field. Additionally, Miao et al (2018) found decreased exploratory activity of spectator pregnant mice in the open arms after successive exposure to mate social defeat.…”
Section: Discussionmentioning
confidence: 99%